The Influence of PBL Model on Student Learning Outcomes in the Form Changes Concept of Substances - Pakaya, Ismail; Abdjul, Tirtawaty; Payu, Citron S.; Yunus, Muhammad (Department of Mathematics and Science Education, Faculty of Teacher Training and Education, University of Mataram. Jurnal Pijar MIPA colaborates with Perkumpulan Pendidik IPA Indonesia Wilayah Nusa Tenggara Barat, 2024)
The problem-based learning (PBL) model is the learning model that prepares students to think critically and analytically. This study investigates the effect of the PBL model on students' academic performance related to the form changes concept of substances. The research adopts an experimental approach, utilizing a one-group pretest-posttest design. Data for the study was collected through tests and analyzed using descriptive and inferential statistics, including normality tests, hypothesis tests, and n-gain analysis. The result of the research for the experimental class had an average score of 85.29, replication 1 scored 84.71, and replication 2 scored 82.56. Additionally, the average normalized gain was 0.72 for the experimental class, 0.73 for replication class 1, and 0.69 for replication class 2, which means that the Replication 1 sample class was higher, while the experimental and control classes were currently in the category. Thus, the PBL model affects student learning outcomes by changing the concept of substances. The research of the PBL model on student learning outcomes is expected to be developed in other material concepts.